Branding in pictures: using Instagram as a brand management tool in professional team sport organisations. Issue 4 (8th August 2018) - Anagnostopoulos, Christos; Parganas, Petros; Chadwick, Simon; Fenton, Alex
ABSTRACT: Research question/purpose: Instagram has become an increasingly popular tool for sport organisations to share visual content. This study aims to examine how professional team sport organisations use Instagram for branding purposes and to explore the meaning of Instagram followers' reactions to the organisations' Instagram activity. Research methods: The study was conducted in two phases. First, we analysed 2017 Instagram photos of two football teams from the English Premier League. Photos were categorised on product- and non-product-related brand attributes. Employing a quantitative content analysis technique, statistical analysis involved intra-case and inter-case relationships between brand attributes and Instagram's key fan engagement features ( Comment and Like ). Second, we analysed 2100 Instagram comments from a qualitative perspective in order to gain further insight into the fans' meanings associated with such posts. Results and findings: The findings offer significant insights to sport marketers in their efforts to increase fan engagement through social media. For both of the examined football teams, product-related attributes were used significantly more often than non-product-related attributes and encouraged greater engagement from online followers. Against these brand attributes, fans' interaction through one of the Instagram's key engagement features is expressed through 'aspiring'-, 'belonging'-, 'criticising'-, and 'loving'-based comments. Implications: The study shows that Instagram facilitates co-branding, while giving fans a more active role in the branding process through comments. We recommend a culture change whereby teams become more market-focused and communications-driven by employing a greater understanding of the semiotics of images and fan comments through the use of social media.